An assessment of the impact of nomadic tourism on sustainable tourism - Kristi, Johann Ananda; Ramzy Damasetio (Institute of Advance Science, Social, and Sustainable Future, 2025)
Background: The development of nomadic tourism, particularly among digital nomads, represents a strategic adaptation by the tourism sector to pandemic conditions that has continued into the post-COVID-19 era. Methods: This study employs a qualitative literature review, synthesizing existing research on digital nomads to assess the social, economic, and environmental impacts of nomadic tourism while evaluating its potential to promote sustainable tourism. Findings: The review reveals that although nomadic tourism shares many characteristics with traditional tourism, differences in travelers' duration of stay and reliance on internet connectivity result in both positive and negative effects on local communities, economic equity, and environmental sustainability. Conclusion: The findings suggest that nomadic tourism can drive sustainable development by fostering equitable community welfare, enhancing oversight of resource utilization, and encouraging deeper cultural engagement among tourists. Novelty/Originality of this article: By linking the adaptive trend of digital nomadism with sustainable tourism development, this study offers innovative insights and policy recommendations that distinguish it from previous research.